2011
DOI: 10.1007/s13314-011-0002-1
|View full text |Cite
|
Sign up to set email alerts
|

Cladosporium oxysporum on Prunus nepalensis in India

Abstract: Prunus nepalensis is grown as a fruit crop in Northeast India. Severe leaf blight was observed on almost 40% of seedlings grown in a polyhouse in Meghalaya, India. Light and scanning electron microscopy revealed the presence of Cladosporium oxysporum, which was confirmed by a pathogenicity test. To our knowledge this is the first report of leaf blight on P. nepalensis caused by C. oxysporum in India Keywords Cladosporium oxysporum . Prunus nepalensis Prunus nepalensis is an important fruit crop grown in Northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Trichoderma is a widespread fungus that is considered as an opportunistic avirulent plant symbiont (Harman et al, 2004;Bae et al, 2011). Previously, reports of Cladosporium oxysporum indicated that it has pathogenic effects on tomato and some vegetables, while it normally causes leaf spot (Wilingham et al, 2002;Baiswar et al, 2011;Zheng et al, 2014). Didymella glomerata is within the Didymellaceae family, which can cause stem lesions or cankers (Chen et al, 2015;Basim et al, 2016;Yao et al, 2016;Donati et al, 2018).…”
Section: Morphological Characteristics and Identification Of Endophytmentioning
confidence: 99%
“…Trichoderma is a widespread fungus that is considered as an opportunistic avirulent plant symbiont (Harman et al, 2004;Bae et al, 2011). Previously, reports of Cladosporium oxysporum indicated that it has pathogenic effects on tomato and some vegetables, while it normally causes leaf spot (Wilingham et al, 2002;Baiswar et al, 2011;Zheng et al, 2014). Didymella glomerata is within the Didymellaceae family, which can cause stem lesions or cankers (Chen et al, 2015;Basim et al, 2016;Yao et al, 2016;Donati et al, 2018).…”
Section: Morphological Characteristics and Identification Of Endophytmentioning
confidence: 99%
“…yBaiswar et al (2011) mencionan a Cladosporium oxysporum como un organismo saprófito y/o patógeno de plantas Bensaci et al (2015). utilizaron suspensiones de conidios de C. oxysporium, endófito aislado de tallos de Euphorbia bupleuroides subsp.…”
unclassified